Orthosis Followed by Trapeziectomy for Thumb Base Osteoarthritis: A Cohort Pilot Study on Pain and Function - Kati Jaatinen, M.Sc; Jenni Pajari, MD; Eero Waris, MD, PhD; Jarkko Jokihaara, MD, PhD; Simo Taimela, MD, PhD; Teppo L.N. Järvinen, MD, PhD; Teemu Karjalainen, MD, PhD (Journal of Hand Surgery Global Online)
Purpose: This study aimed to assess how much symptoms resolve during a 6-week continued nonsurgical treatment with an orthosis and after trapeziectomy in people with thumb carpometacarpal joint osteoarthritis (CMC-1 OA) referred for surgical consultation. The data on symptom resolution magnitude and trajectory can help inform patients about postsurgical recovery and assist researchers in designing clinical trials to evaluate surgery’s effectiveness for CMC-1 OA. Methods: We recruited 52 patients with CMC-1 OA referred for surgical consultation. All eligible and willing patients underwent a 6-week treatment period with an orthosis before trapeziectomy. We collected outcome measures at the time of recruitment, after 6-week use of an orthosis (time of surgery), and at 3, 6, 9, and 12 months following the surgery. The Patient-Rated Wrist/Hand Evaluation questionnaire was the primary outcome measure. We used a repeated measures mixed model to estimate the group mean values for continuous outcomes. We compared the estimates with known minimal clinically important difference values. Results: A continued nonsurgical treatment with a 6-week use of an orthosis resulted in no relief from hand disability and pain. After trapeziectomy, a large and clinically important change occurred at 3 months, and a rapid decrease in symptoms continued until 6 months, at which point it was three times the minimal clinically important difference value for Patient-Rated Wrist/Hand Evaluation. Conclusions: This study provides useful estimates for the trajectory and magnitude of the symptom resolution after trapeziectomy. A continued nonsurgical treatment with a 6-week use of an orthosis had a negligible impact on symptoms in patients who were referred for surgical consultation. In contrast, a large improvement can be expected after trapeziectomy. However, it remains unclear how much of this change is attributable to the surgery itself. Type of study/level of evidence: Therapeutic IIb.